Strategi Peningkatan Kesejahteraan dan Pengelolaan Keuangan Kelompok Tani Kelapa Makmur melalui Pendekatan Arisan sebagai Skema Keuangan Alternatif di Desa Lombang - Dessy Novitasari Laras Asih; Very Andrianingsih; Moh Faisol (Fakultas Sosial dan Ilmu Politik Universitas Wiraraja, 2025)
Lombang Village in Sumenep Regency relies heavily on seasonal agriculture, particularly watermelon and coconut production, resulting in unstable farmer incomes due to market fluctuations and climate change. The